Sistema de tratamento de água salobra : alternativa de combate à escassez hídrica no semi-árido sergipano - Formoso, Silvia Cupertino (2010)
In order to solve scarcity of water in semi-arid regions, many technologies have been studied and tested, presenting positive and negative aspects for each application. In the last years, the Brazilian Government has been trying to supply the water demand of isolated communities of the semi-arid region through the installation of desalination equipments operating through reverse osmosis. However, a good part of the installed devices is out of use, due to maintenance problems. This study tries to point out an alternative of water production which requires simpler operation and maintenance, particularly without the use of filter elements. Solar distillation was used as technologic approach, specially because its characteristics are in agreement with the natural characteristics of insolation of the region. The system was proposed with the objective of supplying a familiar scale water demand and basically consists of a parabolic trough concentrator of solar radiation and a condenser. Through a preliminary economic evaluation, it was achieved a water cost of R$30,00/m3.